Associations between the Healthy Eating Index-2015 and S-Klotho plasma levels: A cross-sectional analysis in middle-to-older aged adults - Ma, Teng-Chi; Zhou, Jing; Wang, Chen-Xi; Lin, Zhi-Zhi; Gao, Feng (Frontiers in Nutrition, 2023)
Background and Aim: The Healthy Eating Index (HEI) is a dietary index developed by the United States Department of Agriculture (USDA) to determine whether a diet adheres to US dietary guidelines. Soluble Klotho (S-Klotho) is a protein with essential anti-aging properties. However, whether HEI is linked to S-Klotho plasma levels is still debatable. This study aimed to assess the association between HEI-2015 and S-Klotho in middle-to-older aged adults in the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2016. Methods: The study included 8456 middle-to-older aged (40-79 years old) participants. Multivariate regression models were used to estimate the correlation between HEI-2015 and S-Klotho concentrations. General additive models and two-piece-wise regression models were used to investigate the possible non-linear relationships between HEI-2015 and S-Klotho concentrations. Moreover, a stratified analysis of potential influencing factors was performed. Results: A positive correlation was observed between HEI-2015 and S-Klotho plasma levels (β = 0.74, 95% CI: 0.21, 1.27, P = 0.0067). According to the two-piece-wise regression, the turning point of HEI-2015 was 45.15. When the range of HEI-2015 was from 0 to 45.15, the relationship between HEI and S-Klotho was insignificant (β = -0.87, 95% CI: -2.47, 0.73, P = 0.2858). However, when the range of HEI-2015 was from 45.15 to 100, HEI-2015 increased by 1 unit, the S-Klotho increased by 1.30 pg/ml (β = 1.30, 95% CI: 0.55, 2.05, P = 0.0007), suggesting a dose-response relationship. Furthermore, the stratified analysis showed that the association between HEI-2015 and S-Klotho concentrations was more significant in people with normal body mass index (P-interaction <0.0001). Conclusion: There is a dose-response relationship between the HEI-2015 and S-Klotho in the middle-to-older aged adults. This relationship suggests that adherence to healthy dietary patterns may benefit the prevention of aging and health maintenance. The underlying mechanisms require further investigation.